The determination of vitamin C in guava (Myrtaceae species) using spectrophotometric approach - Tania Aliansa; Muhammad Abdurrahman Munir; Veriani Aprilia; Emelda Emelda (DAS Institute, 2023)
Vitamin C is one of the essential vitamins for body health. However, vitamin C cannot be produced by the body itself. Thus, to fulfill the vitamin C requirement, it can be obtained by consuming fruits and vegetables. The purpose of this study was to find out and analyze the levels of vitamin C in guava (Psidium guajava L.), crystal guava (Psidium guajava (L.) Merr.), and water guava (Syzygium aquenum). This study used UV-Vis spectrophotometry to analyze the vitamin C content. The results of vitamin C levels in samples such as red guava, crystal guava, and water guava were 21.16 mg/5 g ± 0.005, 20.79 mg/5 g ± 0.029, and 19.16 mg/5 g ± 0.089, respectively. Based on these outcomes, it can be concluded that high levels of vitamin C can be acquired in red guava (Psidium guajava L.)